Obstetrician–Gynecologists' Practices in Postpartum Sterilization Without a Valid Medicaid Consent Form. Issue 1 (July 2021) - Arora, Kavita Shah; Ponsaran, Roselle; Morello, Laura; Katabi, Leila; Behmer Hansen, Rosemary T.; Zite, Nikki; White, Kari
Abstract : OBJECTIVE: To explore the practices of obstetrician–gynecologists (ob-gyns) in the United States surrounding postpartum sterilization when the Medicaid consent form was not valid. METHODS: Using the American College of Obstetricians and Gynecologists' online directory, we conducted a qualitative study where we recruited ob-gyns practicing in 10 geographically diverse U.S. states for a qualitative study using semi-structured interviews conducted by telephone. We analyzed interview transcripts using the constant comparative method and principles of grounded theory. RESULTS: Thirty ob-gyns (63% women, 77% nonsubspecialized, and 53% academic setting) were interviewed. Although most physicians stated that they did not perform sterilizations without a valid Medicaid sterilization form, others noted that they sometimes did due to a sense of ethical obligation toward their patient's health, being in a role with more authority or seniority, interpreting the emergency justification section of the form more broadly, or backdating the form. The physicians who said that they never went ahead without a signed form tended to work at large institutions and were concerned with losing funding and engaging in potentially illegal or fraudulent behavior. CONCLUSION: Physicians' varied behaviors related to providing postpartum sterilization without a valid Medicaid consent form demonstrate that the policy is in need of revision. Unclear terminology and ramifications of the Medicaid sterilization policy need to be addressed to ensure equitable care. Abstract : Obstetrician–gynecologists occasionally perform desired postpartum sterilizations without valid Medicaid consent forms for a variety of ethical reasons.